Sulfide ore facies, fluid inclusion and sulfur isotope characteristics of the Tappehsorkh Zn-Pb ( ± Ag-Ba) deposit, South Esfahan, Iran - Konari, Mina Boveiri; Rastad, Ebrahim; Peter, Jan M.; Choulet, Flavien; Kalender, Leyla; Nakini, Ali (Elsevier Gmbh, 2020)
The stratiform, stratabound Tappehsorkh Zn-Pb (+/- Ag-Ba) deposit, located in the southeastern part of the Malayer-Esfahan Metallogenic Belt of Iran, formed during Lower Cretaceous back-arc extension. Sulfide mineralization occurs within dolostone, black siltstone, and crystal lithic tuff and andesite associated with the Gushfil-Baghabrisham synsedimentary normal fault. Three sulfide ore facies (massive, bedded, and stockwork) occur in the deposit. Sulfide minerals are sphalerite, galena, tetrahedrite and pyrite with minor chalcopyrite and bornite, and gangue minerals are barite, dolomite and quartz. Sulfide mineralization textures are massive, replacement, vein-veinlet, laminated, disseminated, and breccia Three mineralization stages are distinguished: early, main and post-ore. An early fine-grained sulfide ore (early ore, stage I) occurs in the bedded facies which has synsedimentary textures such as laminated, disseminated and framboidal pyrite, galena and sphalerite. Coarse-grained sulfides in the brecciated, massive replacement, and vein-veinlet textures comprise main ore stage of mineralization (main ore, stage II) and formed during diagenesis via sub-seafloor replacement of protore by mixing of hydrothermal brines with cold seawater. Late, coarse-grained sulfides (post-ore, stage III) were formed during deformation and orogenic events and occur as strain fringes, foliation-like, and spindle textures. Pervasive hydrothermal alteration styles are predominantly dolomitization and silicification and minor sericitization occurs in all host rocks in the hanging-wall of the GBF. Fluid inclusions within massive sphalerite of the main ore stage have trapping temperatures ranging from 118-199 degrees C, and salinities ranging from 6.2 to > 23.32 wt. % NaCl equivalent. The delta S-34 values of the sulfide minerals from main ore stage ranges from -2.4 to -34.1%, whereas barite ranges from +10.3 to +16.9 parts per thousand. The negative values of the delta S-34 as well as the narrow range of delta S-34 in galena and sphalerite suggest that sulfur was derived by bacterial reduction of seawater sulfate. The back-arc extensional tectonic setting, presence of a normal fault controlling sulfide mineralization and hydrothermal alteration, the siliciclastic-carbonate-volcanic lithology of the host rocks, magmatism in the region (pyroclastic and volcanic rocks, that also host the sulfide mineralization), the distribution of the three ore facies, and the negative sulfur isotope values all support a sub-seafloor diagenetic replacement SEDEX-type classification for the Tappehsorkh deposit, which was then affected by Laramide (?) orogenic events which imparted the post-ore stage mineral textures.
Keywords: Sulfide ore facies; Back-arc; Hydrothermal alteration; Ore stages; SEDEX-type; Tappehsorkh